STRATEGI PUBLIC RELATIONS MYKO HOTEL & CONVENTION CENTER MAKASSAR DALAM MENYELESAIKAN KRISIS PUBLIK - Citra Ayu Mandiri; Sitti Murniati Mukhtar (KAREBA : Jurnal Ilmu Komunikasi, 2016)
The purpose of this study is (1) To know the public relations strategy of MYKO Hotel & Convention Center Makassar in solving public crisis; (2) To know what factors support the Public Relations of MYKO Hotel & Convention Center Makassar in solving the public crisis. This type of study uses descriptive qualitative study method by presenting data in the form of narrative descriptions, words, phrases, opinions and ideas collected by studyers from various sources. Studyers obtained data based on in-depth interviews with competent sources to answer the problem formulation, where the informants were selected by using purposive determination technique and through literature study based on the data received from the staff of MYKO Hotel & Convention Center. The result of the study shows that the strategy used by PR MYKO Hotel & Convention Center Makassar in solving the public crisis include: conducting study on case and news, completing the licensing documents in accordance with the procedures of Makassar city government, press conference, providing services to the media, invite Makassar city government to come and see the situation of the company, set up crisis center. The supporting factors in solving the public crisis are human resources (HR), cooperation with stakeholders, infrastructure, budget, link building, development of information and communication technology, non-writing activities.  Tujuan studi ini adalah (1) Untuk mengetahui strategi public relations MYKO Hotel & Convention Center Makassar dalam menyelesaikan krisis publik; (2) Untuk mengetahui mengetahui faktor-faktor apa yang mendukung Public Relations MYKO Hotel & Convention Center Makassar dalam menyelesaikan krisis publik.Tipe studi ini menggunakan metode studi deskriptif kualitatif yakni dengan menyajikan data dalam bentuk deskripsi berupa naratif, kata-kata, ungkapan, pendapat dan gagasan yang dikumpulkan oleh penulis dari berbagai sumber. Penulis memperoleh data berdasarkan wawancara mendalam dengan para narasumber yang berkompeten menjawab rumusan masalah, dengan menggunakan teknik penarikan informan secara purposive dan melalui studi pustaka berdasarkan data-data yang terima dari staff MYKO Hotel & Convention Center. Hasil studi menunjukkan bahwa strategi yang digunakan oleh PR MYKO Hotel & Convention Center Makassar dalam menyelesaikan krisis publik antara lain : melakukan study kasus dan pemberitaan, melengkapi dokumen perizinan sesuai prosedur pemerintah kota Makassar, melakukan press conference, pelayanan kepada media, mengundang pemerintah kota Makassar untuk showing perusahaan, mendirikan crisis centre. Adapun faktor-faktor pendukung dalam menyelesaikan krisis publik yakni sumber daya manusia (SDM), kerjasama dengan para stakeholders, sarana prasarana, anggaran, pembentukan link, perkembangan teknologi informasi dan komunikasi, kegiatan non penulisan.